Application of geographical information system in assessing water quality in the Kuantan River Watershed, Malaysia - Ngeow, Kin Voon (2008)
Malaysia has gradually entered its fast pace economic development era following the implementation of the 20 years economy policy in the late 1970s. Due to the rapid urban development, a comprehensive river water quality assessment is required to cope with the dramatic increment of undesirable materials and residues introduced into the river system. A river water quality assessment focusing on suspended solids, sediment, total phosphorus and total nitrogen had been undertaken in Kuantan river watershed. The aim of the study is to determine the pollutant loads and concentration for non-point source pollution while determining the applicability of the geographic information system (GIS) for the water quality study in the Kuantan river watershed. The research involves hydrological and water quality data from the Department of Irrigation and Drainage (DID) and Department of Environment (DOE), topographical digital map from the Department of Land and Survey (JUPEM), and landuse information from the Department of Agriculture (DOA), were loaded onto the geographical information system to represent the variation of pollutant loads emitted from series of non-point pollution sources. Validation works were conducted by comparing between the predicted results and measured results from GIS simulation as well as DID and DOE records for streamflow and water quality data. The validation results for the streamflow in Kuantan river watershed for the year 2005 has a correlation value of r2 = 0.5944 for mean flow condition (p <0.05). The validation results for the pollutant concentration showed the highest correlation values for suspended solids, sediments, total phosphorus and total nitrogen were r2 = 0.6043 in March 2005, r2 = 0.9642 in March 2005, r2 = 0.5806 in July 2005 and r2 = 0.5882 in March 2005, respectively. The lowest correlation values for suspended solids, sediments, total phosphorus and total nitrogen were r2 = 0.1988 in July 2005, r2 = 0.3322 in May 2005, r2 = 0.2341 in January 2005 and r2 = 0.0449 in January 2005 (p <0.05), respectively. Based on the simulation results, the applicability of the GIS is suitable for the water quality study in the Kuantan river watersheds due to moderate correlation values. The existing results have shown that standard GIS functions could be adapted for data manipulations and solving complex water quality problems.